Sistem Pencatatan Laporan Tanam Dan Hasil Panen Menggunakan Sms Gateway Di Wilayah Kabupaten Bandung Barat - Yulianus Palopak; Sharon Aljeazsa Lovelyjeal Silalahi (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
The purpose of establishing System of planting and harvesting reports based on SMS Gateway is as a supporting tool to send information to farmers efficiently and quickly. Information Technology that being used to build SMS Gateway Application for System of Planting and Harvesting Report in Agriculture Department based on PHP and using Gammu as interface that connects mobile phone or modem with computer. As Method Research used SDLC method. This system uses a modem and Mobile as a medium of sending and receiving incoming messages. This system is built by configuring your gammu to work properly, creating a system capable of replying to sms registrations and information with autoreplay. From the results of research and testing that have been implemented, obtained the conclusion that Gammu can be configured with modem and database through device manager. This system can detect incoming messages in the inbox sent by the farmer and can send a reply according to the needs of farmers.